Integrasi Augmented Reality (AR) dalam Pembelajaran Biologi Untuk Meningkatkan Motivasi dan Pemahaman Konsep Siswa SMA Negeri 2 Gunungsitoli - Tektonius Halawa; Toroziduhu Waruwu; Novelina Andriani Zega (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
The integration of Augmented Reality (AR) in biology learning still faces challenges, particularly in improving student motivation and conceptual understanding at the high school level. This study aims to analyze the effect of Augmented Reality integration in biology learning on improving student motivation and conceptual understanding at SMA Negeri 2 Gunungsitoli in the 2024/2025 academic year. This study used a quasi-experimental design with a pretest-posttest control group design involving 60 11th-grade students. Data on learning motivation were collected through a validated motivation questionnaire, while data on conceptual understanding were obtained from a reasoned multiple-choice objective test. Data analysis was performed using MANOVA to test for simultaneous differences and independent-samples t-tests for intergroup comparisons at a significance level of 0.05. The results showed that AR integration significantly increased student learning motivation and conceptual understanding simultaneously (F = 14.583; p < 0.05). Another significant finding was the 47.6% increase in the mean conceptual understanding score of the experimental group compared to the 14.7% increase in the control group.